Reasons behind the availability of family support of older persons in Malaysia - Wan Ahmad, Wan Ibrahim; Ismail, Zainab (IDOSI Publications, 2014)
Family support has been widely assumed to enhance well-being of older persons in society.Many older persons all over the world assumed to receive support from their family members as they become physically dependent.Research conducted in Malaysia suggests family is still the main source of support for the older persons.This article seeks to analyze the reasons why some of the older persons in Malaysia did not receive support from their family members.Data for this study were collected from a survey of 214 respondents aged 60 and above in rural areas in the state of Kelantan, Malaysia.Result of this article reveals that there are five reasons behind the availability of family support, which are whether the respondents having children in their family; whether the adult children leaving in the same locality with the respondents; whether the respondents having daughter with academic achievement; whether the respondents having neighbors nearby; and the pattern of living arrangement of older persons.In general result reveals that family members in the study area still continue to provide care and support for their aged dependents.